2020
DOI: 10.1371/journal.pone.0237083
|View full text |Cite
|
Sign up to set email alerts
|

Quality of hypertension management in public primary care clinics in Malaysia: An update

Abstract: Introduction Adequate control of hypertension is a global challenge and is the key to reduce cardiovascular disease risk factors. This study evaluates management of hypertensive patients in primary care clinics in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Half of the studies in a systematic review reported that the professionals' adherence to clinical guidelines decreased after more than one year of implementation 30 . A recent article reported gaps in guidelines and actual clinical management among hypertensive patients in Malaysia 31 …”
Section: Discussionmentioning
confidence: 99%
“…Half of the studies in a systematic review reported that the professionals' adherence to clinical guidelines decreased after more than one year of implementation 30 . A recent article reported gaps in guidelines and actual clinical management among hypertensive patients in Malaysia 31 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical aspects analyzed demonstrate the high percentage of patients with a prescription for this pathology; thus, both in this study and in the study by Teh et al, almost all individuals had two or more antihypertensive drugs prescribed [ 33 ]. Furthermore, it is notorious that medication time is extended [ 34 ] and usually accompanies the time to diagnosis [ 30 ].…”
Section: Discussionmentioning
confidence: 84%
“…Fatalism (items 7,8,12,15,24,30,33,35,and 45) that enables us to know if the patient sees the diagnosis as a minor threat with absent attitudes of confrontation and serenity about the results-passive acceptance; -Avoidance/denial (items 38) understood as the refusal of diagnosis or admission of diagnosis but denying the severity with a positive view of the prognosis in which the issue of control is irrelevant.…”
mentioning
confidence: 99%
“…MyHEBAT-CRES recruited participants through nationwide sampling which covered urban/rural areas in 11 states of Malaysia. Instead of targeting participants with a specific disease or condition, MyHEBAT-CRES recruited Malaysian participants with or without known health status, since several studies in Malaysia indicated that Malaysians lacked awareness of their health status and were unaware of which risk factors contributed to CVD [ 5 , 7 , 27 , 35 ].…”
Section: Malaysian Health and Wellbeing Assessment (Myhebat)mentioning
confidence: 99%